Etiology and Short term Outcome of Acute Kidney Injury (AKI) in Hospitalized Patients : A Single Center Study - Mahbub, Tania; Niger, Chowdhury Rifat; Khanam, Rawshan Arra; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2019)
Acute Kidney Injury (AKI) is a common cause of morbidity and mortality worldwide. However it is a treatablecondition. Any disease when associated with AKI, mortality and morbidity increase manifolds.1 Early diagnosis andtreatment is important to reduce morbidity, mortality and ICU admission. Causes of AKI may vary in country to countryeven within the country. International society of Nephrology has set a high ambitious goal “0 by 25” targeting zerodeath due to untreated AKI by 2025. Heading this challenge, it is important to know the causes of AKI worldwide.However, most of the AKI studies have been done in the developed countries and limited information is availableregarding Asia, Africa and south America. Inspired by this slogan, this study was directed to find out the causes of AKIin admitted patients in United Hospital Limited between July 2015 to February 2017. Total 98 patients were includedin the study. In our study, Infection and cardio-renal syndrome were the leading causes of AKI. Drug induced AKI alsocontributed a significant portion. Bangladesh Crit Care J September 2019; 7(2): 77-80